Is Antral Wash Out Really Indicated in Acute Bacterial Rhino Sinusitis? - KC, Toran (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Key words: sinusitis; antral wash out; conservative treatment DOI: 10.3126/njenthns.v1i1.4730 Nepalese J ENT Head Neck Surg Vol.1 No.1 (2010) p.12-13